Cover Feature: Intramolecular [2+2] Cycloaddition of N‐Allylcinnamamines and N‐Allylcinnamamides by Visible‐Light Photocatalysis (Eur. J. Org. Chem. 1/2020). Issue 1 (19th December 2019) - Oderinde, Martins S.; Kempson, James; Smith, Daniel; Meanwell, Nicholas A.; Mao, Edna; Pawluczyk, Joseph; Vetrichelvan, Muthalagu; Pitchai, Manivel; Karmakar, Ananta; Rampulla, Richard; Li, Jianqing; Murali Dhar, T. G.; et al.
Abstract : The Cover Feature shows the [2+2] photocycloaddition of highly functionalized N ‐allylcinnamamides and N ‐allylcinnamamines, that could provide the corresponding aryl‐3‐azabicyclo[3.2.0]heptanones and aryl‐3‐azabicyclo[3.2.0]heptanes, respectively. Those compounds are useful as both scaffolds and fragments in drug design and discovery. We thank Dr. John Tokarski at BMS and Accdon, LLC/ LetPub for the cover design. More information can be found in the Full Paper by M. S. Oderinde et al.